PERAN AUDITOR INTERNAL DALAM MEWUJUDKAN KEPATUHAN ORGANISASI PERANGKAT DAERAH (OPD) DI BIDANG PENATAUSAHAAN KEUANGAN PADA KANTOR INSPEKTORAT KABUPATEN MINAHASA UTARA - Anjali, Andini; Morasa, Jenny; Walandouw, Stanley Kho (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
The role of internal audit in this case is that government internal auditors play an important role in the government system, namely as a supervisory function where the internal auditors are given the responsibility of examining, evaluating and carrying out the supervisory function. This study aims to determine the role of the Inspectorate as an internal government auditor in realizing the compliance of Regional Apparatus Organizations (OPD) in the field of financial administration. Data collection techniques using interviews and documentation. Based on the research results, it is known that the Inspectorate of North Minahasa Regency as the government's internal auditor has a very important role in supervising the financial administration sector. This is evidenced by the implementation of the supervisory function in internal audit, namely planning the supervision program, formulating policies and monitoring facilities as well as examining, investigating, testing and evaluating the supervisory duties as well as monitoring performance and finance by the Regional Apparatus Organization (OPD) in North Minahasa Regency. Apart from overseeing and examining the government internal auditors also play a role in detecting fraud.